Store-operated Ca2+ influx in airway smooth muscle - Interactions between volatile anesthetic and cyclic nucleotide effects - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2006)
Background Volatile anesthetics produce bronchodilation in part by depleting sarcoplasmic reticulum Ca2+ stores in airway smooth muscle (ASM). Other bronchodilatory drugs are known to act via cyclic nucleotides (cyclic adenosine 3',5'-cyclic monophosphate, cyclic guanosine 3',5'-cyclic monophosphate). Intracellular Ca2+ regulation in ASM involves plasma membrane Ca2+ influx, including that triggered by sarcoplasmic reticulum Ca2+ depletion (store-operated Ca2+ entry [SOLED. The authors hypothesized that anesthetics and bronchodilatory agents interact in inhibiting SOLE, thus enhancing ASM relaxation. Methods: In enzymatically dissociated porcine ASM cells imaged using fluorescence microscopy, sarcoplasmic reticulum Ca2+ was depleted by 1 mu M cyclopiazonic acid in 0 extracellular Ca2+, nifedipine, and potassium chloride (preventing Ca2+ in-flux through L-type channels and SOLE). Extracellular Ca2+ was rapidly reintroduced to selectively activate SOLE in the presence or absence of 1 minimum alveolar concentration (MAC) halothane, isoflurane, or sevoflurane. Anesthetic interference with SOLE regulation by cyclic nucleotides was examined by activating SOLE in the presence of (1) 1 mu M acetylcholine, (2) 100 mu M dibutryl cyclic adenosine 3',5'-cyclic monophosphate, or (3) 100 mu M 8-bromo-cyclic guanosine 3',5'-cyclic monophosphate. Results: SOLE was enhanced by acetylcholine, whereas volatile anesthetics and both cyclic nucleotides partially inhibited Ca2+ influx. Preexposure m 1 or 2 MAC anesthetic (halothane > isoflurane > sevoflurane) inhibited SOLE. Only halothane and isoflurane inhibited acetylcholine-induced augmentation of Ca2+ influx, and significantly potentiated cyclic nucleotide inhibition such that no influx was observed in the presence of anesthetics and cyclic nucleotides. Conclusions: These data indicate that volatile anesthetics prevent sarcoplasmic reticulum refilling by inhibiting SOLE and enhancing cyclic nucleotide blunting of Ca2+ influx in ASM. Such interactions likely result in substantial airway relaxation in the presence of both anesthetics and bronchodilatory agents such as beta agonists or nitric oxide.
Keywords: CAPACITATIVE CALCIUM-ENTRY; MUSCARINIC RECEPTOR STIMULATION; PORTAL-VEIN MYOCYTES; PULMONARY-ARTERY; NITRIC-OXIDE; CELLS; CHANNELS; HALOTHANE; MECHANISMS; CONTRACTION